Model Pembelajaran INITIATIVE dengan Pendekatan Kontruktivisme Berbasis Komunitas Remaja Masjid Pascapandemi Covid-19 - Andika Hendra Mustaqim; Rina Lestari; Suci Riyanti; Arrizqi Ramadhan (Randang Tana - Jurnal Pengabdian Masyarakat, 2022)
After two years of the Covid-19 pandemic, the world is starting to move, as shown by the face-to-face learning process that has begun, including in empowering communities such as the Jami' Al Muttaqin Mosque Youth in Jakarta. The problem that partners face is the ability to communicate in English which is increasingly needed. The purpose of research-based community service development of learning models for teenagers at the Jami' Al Muttaqin Mosque in Jakarta is learning English, especially about Adjective to Express Personality and Appearance. The result of community service is to produce a learning model developed by researchers under the name INITIATIVE. It is a learning model that has elements such as Idealism, Neologism, Incrementalism, Tachism, Intuitionism, Activism, Territorialism, Instrumentalism, Vocationalism, and Essentialism. It has been applied in the community service process. The model is considered appropriate to be practiced in post-Covid-19 learning because it prioritizes creativity and innovation. The paradigm used in this model is constructivist based on critical reality in education. The model not only focuses primarily on students, but involves educators and other actors, namely institutions, both schools and communities